2003
DOI: 10.1089/105072503322511328
|View full text |Cite
|
Sign up to set email alerts
|

Production and Application of Polyclonal Antibody to Human Thyroid Transcription Factor 2 Reveals Thyroid Transcription Factor 2 Protein Expression in Adult Thyroid and Hair Follicles and Prepubertal Testis

Abstract: Germline mutations in thyroid transcription factor 2 (TTF2) cause thyroid agenesis, spiky hair, and cleft palate, indicating thyroidal and extrathyroidal expression. We sought to investigate this by producing and applying an antibody to human TTF2. The coding region of human TTF2 was cloned into a bacterial expression vector, production of the soluble TTF2 protein optimized, and pure TTF2 obtained by nickel chromatography. Rabbits were immunized and the resulting TTF2 polyclonal titrated on formalin-fixed, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…23 The importance of these three transcription factors is evidenced by congenital thyroid agenesis, which results from mutations in any of the transcription factors. [26][27][28][29][30][31][32] We found consistent nuclear expressions of Pax8, TTF-1, and TTF-2 in well-differentiated neoplasms of follicular cell origin, that is, papillary carcinomas, follicular adenomas, follicular carcinomas, and poorly differentiated carcinomas. Seventy-nine percent of anaplastic carcinomas variably showed Pax8 reaction, whereas TTF-1 and TTF2 were expressed in only 18 and 7% of anaplastic carcinomas, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…23 The importance of these three transcription factors is evidenced by congenital thyroid agenesis, which results from mutations in any of the transcription factors. [26][27][28][29][30][31][32] We found consistent nuclear expressions of Pax8, TTF-1, and TTF-2 in well-differentiated neoplasms of follicular cell origin, that is, papillary carcinomas, follicular adenomas, follicular carcinomas, and poorly differentiated carcinomas. Seventy-nine percent of anaplastic carcinomas variably showed Pax8 reaction, whereas TTF-1 and TTF2 were expressed in only 18 and 7% of anaplastic carcinomas, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…15,70 Thyroid transcrip- tion factor 2 expression is restricted to the thyroid; anterior pituitary; epithelia of the oropharynx, trachea, and esophagus; exocrine cells of the seminiferous tubules of the testis; and epidermis and hair follicles. 12,[71][72][73][74][75][76][77][78] Thyroid transcription factor 2 is 1 of 3 TTFs that play critical roles in thyroid organogenesis and differentiation. However, TTF2 seems to play a role in the development of the negative controller of thyroid-specific gene expression.…”
Section: Thyroid Transcription Factormentioning
confidence: 99%
“…151 In humans, FOXE1 is expressed in the thyroid, foregut embryonic thymus, 49 in the outer follicular hair sheath, and in the seminiferous tubules of prepubertal testis. 155 Studies in mutant mice have shown that Foxe1 is tightly regulated in the thyroid bud by Pax8 and in the pharyngeal cells by Shh. 50 Notably, in keratinocytes Fox1 is a direct target of Gli2, a key mediator of Shh signaling.…”
Section: Foxe1mentioning
confidence: 99%